Characterization of Insertions of IS476 and Two Newly Identified Insertion Sequences, IS1478 and IS1479, in Xanthomonas campestris pv. campestris - Chen, Jiann-Hwa (American Society for Microbiology, 1999)
Thirty-two plasmid insertion mutants were independently isolated from two strains of Xanthomonas campestris pv. campestris in Taiwan. Of the 32 mutants, 14 (44%), 8 (25%), and 4 (12%) mutants resulted from separate insertions of an IS3 family member, IS476, and two new insertion sequences (IS), IS1478 and IS1479. While IS1478 does not have significant sequence homology with any IS elements in the EMBL/GenBank/DDBJ database, IS1479 demonstrated 73% sequence homology with IS1051 in X. campestris pv. dieffenbachiae, 62% homology with IS52 in Pseudomonas syringae pv. glycinea, and 60% homology with IS5 in Escherichia coli. Based on the predicted transposase sequences as well as the terminal nucleotide sequences, IS1478 by itself constitutes a new subfamily of the widespread IS5 family, whereas IS1479, along with IS1051, IS52, and IS5, belongs to the IS5 subfamily of the IS5 family. All but one of the IS476 insertions had duplications of 4 bp at the target sites without sequence preference and were randomly distributed. An IS476 insertion carried a duplication of 952 bp at the target site. A model for generating these long direct repeats is proposed. Insertions of IS1478 and IS1479, on the other hand, were not random, and IS1478 and IS1479 each showed conservation of PyPuNTTA and PyTAPu sequences (Py is a pyrimidine, Pu is a purine, and N is any nucleotide) for duplications at the target sites. The results of Southern blot hybridization analysis indicated that multiple copies of IS476, IS1478, and IS1479 are present in the genomes of all seven X. campestris pv. campestris strains tested and several X. campestris pathovars.